Social-Emotional Learning: Preschool Teachers’ Perspectives from Urban and Rural Contexts - Lasi, Seema; Khan, Khushal; Afzal, Noreen (JECCE, 2023)
Social-emotional learning (SEL) is an integral part of holistic child development. The early years of life are the best window of opportunity when children acquire self-regulation and executive functioning which stays with them throughout their lives. A qualitative exploratory design was implemented employing focus group discussions (FGDs) to understand preschool teachers’ perspectives on SEL from urban and rural areas of Pakistan. Five (5) FGDs were organized, each with 8 to 10 teachers. Some great insights were highlighted by teachers from urban and rural contexts. Urban schoolteachers demonstrated a better understanding of SEL as compared to rural schoolteachers. The main themes identified during the analysis were teachers' perspectives on; the importance of social-emotional skills for school readiness, adjustment problems faced by newly enrolled children due to lack of social-emotional skills, existing school practices for the promotion of SEL, and how teachers can contribute to building SEL among preschool children. The study provided some great insights and a way forward to foster social-emotional learning among preschool children. Teachers underscored the importance of parents, curriculum, and teacher training for the promotion of social-emotional learning among preschool children. Urban-rural disparities were profound where urban teachers were found to be more aware of the social-emotional needs of preschool children and classroom management required for optimal learning experience.